Structural parameters versus third-order optical susceptibility of zinc porphyrin molecules - Amina, Yasin; Nair, Vijayakumar S.; Mohd Hasbi, Ab. Rahim; Yamaoka, Yoshihisa; Yelleswarapu, Chandra S.; Jose, Rajan (Royal Society of Chemistry, 2021)
To deepen the structure-property relationship, and thereby develop improved third-order nonlinear optical (NLO) molecular materials, porphyrin is a promising candidate because of its strong excited state absorption, high triplet yields, and large transmission window of the main ground state absorption bands. Herein, the third-order NLO properties of molecularly engineered π-expanded Zn(ii)porphyrins (Por-Cn-RAm, wheren= 12 or 8 andm= 1-4) are evaluated by open and closed aperture Z-scan techniques using nanosecond laser pulses and the results are compared with DFT calculations. The measured nonlinear reverse saturable absorption and self-defocusing effect varied in the order Por-C12-RA1> Por-C8-RA4> Por-C12-RA2> Por-C12-RA3, thereby indicating that zinc porphyrins of lesser π-electron conjugation exhibit higher third-order NLO characteristics. The Por-C12-RA1, with a planar structure (dihedral angle:ϕ= 1.38°) and the lowest number of resonating structures, showed much higher third-order NLO parameters than conventional zinc phthalocyanine and the other studied porphyrins. This observation is against the general understanding that extensive π-electron conjugation exhibits stronger third-order NLO properties. Considering these observations, the structure-property relationship in these porphyrins is investigated by combining the experimental results and DFT calculations using six strategies: the effect of (i) lone/unshared pairs of electrons in the molecule, (ii) resonating structures of the molecule, (iii) structural planarity, (iv) position of meso-aryl substituents, (v) electronegativity of the substituents, and (vi) symmetry of the molecule. Among them, the number of free unshared pairs of electrons and the high structural planarity of the molecules along with π-conjugation are shown to be the dominant factors rather than only π-conjugation extension. The findings provide an ideal platform to guide the rational design of new molecules with higher NLO responses